1995
DOI: 10.1088/0953-8984/7/14/019
|View full text |Cite
|
Sign up to set email alerts
|

Internal ionization of Ar and Kr noble-gas cryocrystals by the excitation energy of trapped metastable excited atoms

Abstract: Local metastable excited states are found in Ar and Kr cryocrystals when He gas-discharge products are trapped in the growing cryocrystals. These states are detected by ESR and are interpreted as being local metastable excited np5(n+1)s3P2 atomic-type states in Ar and Kr cryocrystals. The study showed that the yield of the 3P2 excitations in the above process decreases with increasing temperature. Analysis of the results allows the following explanation of the observed effect to be given. Metastable excited He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 1 publication
6
15
0
Order By: Relevance
“…Newly obtained results suggest a new interpretation of the earlier findings [1][2][3]. The interpretation gives insight not only into the emergence of the unstable signals but also into the absence of the g-factor matrix shift.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…Newly obtained results suggest a new interpretation of the earlier findings [1][2][3]. The interpretation gives insight not only into the emergence of the unstable signals but also into the absence of the g-factor matrix shift.…”
Section: Introductionsupporting
confidence: 54%
“…The measurements showed that g-factors of signals from different rare gases were equal within 0.0001. A suggestion put forward [1][2][3] about the splitting of the 3 P 2 atom levels by a strong anisotropic crystal field may, in principle, explain the absence of the matrix shift, but the g-factor in that case should be very close to the free electron g-factor: g e ¼ 2.0023 which differs from the measured quantity.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations